Траектории деинфантилизации: из опыта этнорегиональных исследований / М. Н. Губогло, С. К. Смирнова - Губогло Михаил Николаевич; Смирнова Светлана Константиновна (2006)
Экземпляры: ф.10 (2006) / Инвентарный номер: 49848 / Цена: / Сис.шифр: 63.5(2Рос.Удм) / Авт.знак: Ф 42 / ГРНТИ: 11 / ББК: 66.5(2А/Э)